Implementation of Mamdani Method Fuzzy System in Determining Final Semester Grades of UIN Walisongo Semarang Students - Rezky Aprilianto, Arif; Budi Cahyono; Mohamad Tafrikan (Contemporary Mathematics and Applications (ConMathA), 2025)
Final semester grades are an important component for students to obtain a pass in completing a course. The program for determining final semester grades using fuzzy Mamdani can be used to facilitate the calculation of final semester grades. This research aims to determine the results of applying the Mamdani fuzzy system method in determining the final semester grades of students at UIN Walisongo Semarang. The Mamdani fuzzy system method was chosen as the method for calculating final semester grades along with MAPE (Mean Absolute Percentage Error) calculations. In accordance with the lecture contract for the computational mathematics course, several input variables were found to be used in the research, namely structured assignment grades (20%), independent assignment grades (30%), mid-semester exam grades (25%), and final semester exam scores (25%). The data is processed in several steps, namely creating fuzzy membership sets and functions, creating fuzzy rules, fuzzification, and defuzzification. After calculating with the Mamdani method fuzzy system, the next step is to calculate the MAPE value and display the results. The MAPE value obtained from research with 46 data was 2.074; This means that according to the MAPE criteria it produces accurate data. This proves that the Mamdani fuzzy system method can be applied to calculate students' final semester grades.